Subthreshold diode micropulse photocoagulation for the treatment of clinically significant diabetic macular oedema. Issue 1 (21st December 2004) - Luttrull, J K; Musch, D C; Mainster, M A
Abstract : Aim: To report the visual and clinical outcomes of a pilot study of subthreshold diode micropulse (SDM) laser photocoagulation for clinically significant diabetic macular oedema (CSMO). Methods: The results of infrared (810 nm) SDM laser photocoagulation for CSMO were retrospectively reviewed in 95 eyes of 69 consecutive patients with mild to moderate non-proliferative diabetic retinopathy. The same laser parameters were used for each patient. Only the number of laser applications varied between patients, depending on their macular findings. Primary outcome measures were Snellen visual acuity, fluorescein angiographic leakage, and CSMO status. Results: Visual acuity was stable or improved in 85% of treated eyes, with a mean follow up of 12.2 months (range 3–29 months). CSMO decreased in 96% and resolved in 79% of treated eyes. No adverse laser events occurred. No laser lesions were detectable ophthalmoscopically or angiographically after treatment, consistent with calculations based on ANSI Z136.1 laser safety standards suggestive of only histologically detectable tissue effects at the laser exposure levels. No laser scarring was observed during the follow up period. Conclusion: Subthreshold diode micropulse laser photocoagulation minimises chorioretinal damage in the management of CSMO and demonstrates a beneficial effect on visual acuity and CSMO resolution. Prospective studies are needed to fully evaluate this technique.